Monetary Policy in Emerging Markets : Taming the Cycle - McGettigan, Donal (IMF Working Papers; Working Paper, 2013)
In contrast to advanced markets (AMs), procyclical monetary policy has been a problem for emerging markets (EMs), with macroeconomic policies amplifying economic upswings and deepening downturns. The stark difference in policy has not been subject to extensive study and this paper attempts to address the gap. Key findings, using a large sample of EMs over the past 50 years, are: (i) EMs have adopted increasingly countercyclical monetary policy over time, although large differences remain among EMs and policies became more procyclical during the recent crisis. (ii) Inflation targeting and better institutions have been key factors behind the move to countercyclicality. (iii) Only deep financial markets allow EMs with flexible exchange rate regimes turn countercyclical. (iv) More countercyclical policy is associated with far less volatile output. The economically meaningful impact of IT on monetary policy countercyclicality and output variability is another reason in its favor, over and above better inflation outcomes.